2021
DOI: 10.5204/ssj.1762
|View full text |Cite
|
Sign up to set email alerts
|

“My Uni Experience Wasn’t Completely Ruined”: The Impacts of COVID-19 on the First-Year Experience

Abstract: The first year at university is always challenging, but particularly in 2020 when COVID-19 triggered lockdowns and a rapid shift to online learning. This mixed methods study tracked the wellbeing and engagement of 60 new students in an undergraduate teacher education program at an Australian university throughout the first trimester of 2020. Follow-up focus groups with 14 students used interview and photo elicitation to explore how COVID-19 influenced wellbeing and engagement. Quantitative results demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Difficult living situations were most likely to reduce confidence in learning during ERT (Bartolic et al, 2022 ; Guppy et al, 2022 ). However, students seemed to build new routines for online learning as a result of their early experiences that perhaps, in part, explain the recovery in self-efficacy and wellbeing reported by other researchers as the pandemic continued (Camfield et al, 2021 ; McKay et al, 2021 ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Difficult living situations were most likely to reduce confidence in learning during ERT (Bartolic et al, 2022 ; Guppy et al, 2022 ). However, students seemed to build new routines for online learning as a result of their early experiences that perhaps, in part, explain the recovery in self-efficacy and wellbeing reported by other researchers as the pandemic continued (Camfield et al, 2021 ; McKay et al, 2021 ).…”
Section: Discussionmentioning
confidence: 95%
“…Camfield et al (2021) employed the lens of student self-efficacy and noted that while students lost some sense of agency and belonging, they recovered as time went on with inputs from their instructors. Similarly, McKay et al (2021) showed that first-year student wellbeing and engagement initially dropped with ERT and lockdown but recovered through personal strategies like humour, making strategic decisions, and actively seeking help from others. In addition, Wilson et al (2020), through an autoethnographic approach, showed how self-awareness and self-accountability were important to reduce students' feelings of disconnection, while highlighting that such self-regulation is mediated by emotions and external factors.…”
Section: Research In Emergency Remote Teachingmentioning
confidence: 96%
See 1 more Smart Citation
“…It is a big test for the mental health and well-being of students. While going to university is an exciting time, it has also been well documented as challenging (Baik et al, 2015, in McKay, O`Bryan, andKahu, 2021). Students have a plenty of changes to manage, including making new relationships, living apart from friends and family, acquiring new study skills, and learning to function as independent adults.…”
Section: Introductionmentioning
confidence: 99%
“…The challenges for HE students who study online, remotely from their university, are well documented and include feelings of isolation, lack of dedicated study times and spaces, problems communicating with teachers and other students, poor course design, and technology issues (Devlin & McKay, 2016;McKay et al, 2021;Moore & Greenland, 2017;Ragusa & Crampton, 2018;Stone, 2019). Across regional Australia, home internet connection is a particular concern with many regional areas experiencing poor and unreliable internet provision (Attree, 2021;Stone & Davis, 2020).…”
Section: Introductionmentioning
confidence: 99%